Microsoft Windows Vista administration - Velte, Anthony T.; Glendenning, Dennis R. (Dennis Robert).; Velte, Toby J. (New York McGraw-Hill, 2007)
A guide to Windows Vista administration describes how to design and implement installation and migration plans, create network connections, set up Internet services, use remote access features, and secure PCs and networks.
Keywords: Microsoft Windows. (Computer file).; Microsoft Windows (Computer software); Computer networks -- Management; Computer operating systems